Structural, optical, thermal and mechanical characterization of an organic nonlinear optical material: 4-methyl-3-nitrobenzoic acid single crystal. (November 2016) - Bharathi, M. Divya; Ahila, G.; Mohana, J.; Chakkaravarthi, G.; Anbalagan, G.
Abstract: Organic single crystals of 4-methyl-3-nitrobenzoic acid (4M3N) have been grown by slow evaporation solution growth technique at room temperature. The single crystal X-ray diffraction study reveals that 4M3N crystallizes in monoclinic system with space group P 21/ n . The crystalline perfection of the crystal was analyzed by high resolution X-ray diffraction (HRXRD) measurements. The functional groups present in 4M3N have been identified from FT-IR and FT-Raman spectra. The lower cut-off wavelength of 4M3N is found to be 404 nm and the optical band gap is calculated as 2.91 eV. The refractive index shows normal behavior with wavelength. The physio chemical changes, decomposition and stability of the 4M3N compound were established by TG-DTA studies. Vickers microhardness measurement concludes that 4M3N belongs to soft material ( n =2.5) category. The LDT value is found to be higher than that of KDP and some of the important organic NLO materials. The third order nonlinear refractive index and nonlinear absorption coefficient of the 4M3N have been measured by Z-scan studies. The imaginary and real parts of the third-order susceptibility values were determined as Im χ 3 =9.129×10 −11 esu and Re χ 3 =1.4034×10 −9 esu respectively. The dislocation density was calculated to be 3.0448×10 6 cm −2 which indicates the quality of the crystal. Graphical abstract: Highlights: Single crystal of 4M3N size upto 32×7×7 mm 3 was grown by solution growth method. The structure of the crystal was solved from single crystal data. The crystal shows good transparency in the visible region. Enhanced nonlinear susceptibility and polarizability leads the large third order NLO properties. The LDT value is found to be higher than that of KDP and some of the important organic NLO materials.